Correlation between PPARγ protein expression level in granulosa cells and pregnancy rate in IVF program - Mehdi Sahmani; Reza Najafipour; Laya Farzadi; Ebrahim Sakhinia; Masoud Darabi; Vahideh Shahnazi; Amir Mehdizadeh; Maghsod Shaaker; Mohammad Noori (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2012)
Background: Peroxisome proliferative-activated receptors (PPARs) are nuclear receptors that involved in cellular lipid metabolism and differentiation. The subtype γ of the PPAR family (PPARγ) plays important roles in physiologic functions of ovaries.Objective: To determine correlation between PPARγ protein level in granulosa cells and pregnancy rate in women undergoing in-vitro fertilization (IVF) treatment.Materials and Methods: In this cross-sectional study, twenty-five samples of granulosa cells were collected from women referred to an IVF treatment center. PPARγ protein expression level in granulosa cells was determined in comparison with β-actin level as control gene with Western blot test. Laboratory pregnancy was determined by a rise in blood β-hCG level fourteen days after embryo transfer. Correlation analyses were used to test for associations between the oocytes and pregnancy occurrence as outcome variables and PPARγ protein expression level.Results: Correlation analysis indicated that there was no significant relationship between granulosa cells PPARγ protein level with IVF parameters including number of matured oocytes and the ratio of fertilized to matured oocytes. Comparison of granulosa cells PPARγ protein level with positive and negative laboratory pregnancy revealed also no significant relationship. Conclusion: According to the results of this study, PPARγ protein level in granulosa cells could not be directly correlated to the success rate of IVF.